Circulatory collapse in a parturient undergoing cesarean delivery: a diagnostic dilemma. (May 2017) - Tawfik, M.M.; Taman, M.E.; Tarbay, A.I.; Sayed, M.; Awad, K.A.
Highlights: Massive pulmonary embolism during cesarean delivery carries a high risk of maternal mortality. Differential diagnosis includes thromboembolism, air embolism, and amniotic fluid embolism. Echocardiography assists the clinical diagnosis, excluding other causes of hemodynamic instability. Thrombolysis in the perioperative period requires a plan to manage severe bleeding. Abstract: Embolic events including thromboembolism, air embolism, and amniotic fluid embolism can cause cardiovascular collapse during cesarean delivery. Differentiation between the three conditions is challenging because they share many of the initial clinical and echocardiographic findings, but an accurate, definitive diagnosis allows the administration of specific therapy that may help in saving the life of the mother and/or the fetus. We report a case of cardiovascular collapse during cesarean delivery under general anesthesia; massive pulmonary thromboembolism was suspected and unfractionated heparin was administered. Cardiac arrest followed and was managed with standard cardiopulmonary resuscitation, resulting in return of spontaneous circulation. Postoperatively, the patient remained hemodynamically unstable in spite of heparin, norepinephrine infusions and intravenous fluids. A transthoracic echocardiogram revealed right-sided pressure overload. Thrombolysis was initiated. Streptokinase (1, 500, 000 IU over 2 hours) was administered with no clinical response, followed by infusion (100, 000 IU/h) for 12 hours. The patient's hemodynamics improved gradually and she was successfully weaned from norepinephrine and mechanical ventilation. Significant bleeding ensued, necessitating discontinuation of anticoagulation and transfusion of red blood cells. Eventually, the patient was discharged home, in good condition, and on oral warfarin therapy.